(untitled) (Research, Society and Development, 2020)
This work aims to reflect on the conception of reading that guides the proposals for the activity of the textbook: Portuguese languages, from theoretical assumptions of the social semiotics, in dialogue with the dialogical theory/analysis of Discourse, extending to some of its debaters and studies developed in the field of Textual linguistics among others. For this, we selected three reading proposals, which can show that conception and what reading practices are adopted in the didactic material. Our general objective is to investigate the reading practices of multimodal texts proposed by the textbook in question, In order to reflect on the conception of underlying reading, as well as about its contribution or not to the construction of meanings. Methodologically, this study is subsified by the qualitative approach, characterized as a bibliographic research, of descriptive and interpretative data analysis procedures. Thus, the corpus of this work is constituted on the orientations for reading activities of multimodal texts. The results of our analysis indicate that despite assuming a discursive perspective regarding reading, there is still a very sharp direction for the use of the text as a pretext for the mere grammatical classification, as well as for the exploitation of non-verbal texts, whose activities, in most cases, are still of superficial questions. In this case, the metalinguages are reflected as tools that can lead to reading and, consequently, the expansion of learning for the integration of social and cultural literacy.